A Study of Prospective Primary School Teachers' Alternatif Conception in Heat and Temperature. (November 2019) - Hermita, N; Alpusari, M; Noviana, E; Kurniaman, O; Widyanthi, A; Suhandi, A
Abstract: The aim of the study was to descibe of the alternative conception of prospective primary school teachers related to concept of heat and temperature. This study uses the quantitative descriptive method. This study was conducted on 34 prospective primary school teachers at one university in Riau Province who had attended the basic concepts of science course. The university is located in the coastal area of Riau province. The instrument used to collect data is a conception test in the form of true/false choices accompanied by an explanation of the answers. Based on the choice of true/false answers and explanations given by prospective elementary school teachers, the alternative conceptions they have can be determined. The results showed that there were a number of alternative conceptions owned by prospective elementary school teacher students related to the concept of heat and temperature, where some of the alternative conceptions led to a state of misconception.